2005
DOI: 10.1007/s10227-005-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Imiquimod and 5-Fluorouracil for the Treatment of Actinic Keratosis: Critical Review and Meta-analysis of Efficacy Studies

Abstract: The results of this meta-analysis show that both imiquimod and 5-fluorouracil are effective methods for the treatment of actinic keratosis and provide a useful alternative to cryotherapy. However, this analysis suggests that imiquimod may have higher efficacy than 5-fluorouracil for actinic keratosis lesions located on the face and scalp and therefore provides another option to dermatologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 46 publications
(85 reference statements)
0
19
0
3
Order By: Relevance
“…Some of these were narrative [43] or naïve meta-analyses [22] which are open to risk of bias [44]. Two studies performed meta-analyses of placebo-controlled studies of IMI 5% (16-week course) [45], [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these were narrative [43] or naïve meta-analyses [22] which are open to risk of bias [44]. Two studies performed meta-analyses of placebo-controlled studies of IMI 5% (16-week course) [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with 5% 5-fluorouracil (5-FU) was also considered. However, because the only included study [21] with this treatment was very small and reported a clearance rate (23 out of 24 patients) that was not consistent with the literature [22], this treatment was not included in the NMA.…”
Section: Methodsmentioning
confidence: 99%
“…2,4 Both approaches have been well compared with other therapeutic options, especially 5-fluorouracil, 7,9,11 cryotherapy, 5,9,18 and diclofenac. 10 The only study comparing PDT with imiquimod 12 analyzed AK on the arms; therefore, conclusions cannot be drawn for AK on the face and scalp, which are the most common sites of these lesions.…”
Section: Discussionmentioning
confidence: 98%
“…They also provide a longer recurrence-free period. [2][3][4] Several studies compare PDT [5][6][7][8] and imiquimod [9][10][11] with other treatments for AK, however, few studies to date have compared PDT and imiquimod. Sotiriou et al 12 compared 5-aminolevulinic acid PDT with imiquimod 5% cream for the treatment of AK on the arms in a series of 30 patients; however, their results cannot be extrapolated to the most frequently affected parts of the body, namely, the face and scalp.…”
mentioning
confidence: 98%
“…Preclinical and clinical studies of plant derived terpene agents, including ingenol mebutate derived fromthesap of Euphorbia peplus [1] andMelaleuca alternifolia (teatree) oil [2], have demonstrated the potential for these topical chemotherapies to exert a rapid anti-cancer effect after a relatively short treatment protocol. Long treatment regimes, incomplete clearance rates, poor cosmetic outcomes and systemic toxicity have unfortunately limited patient satisfaction with currently approved topical chemotherapeutics such as imiquimod and 5-fluorouracil [3,4].…”
Section: Introductionmentioning
confidence: 99%